Art and politics in Duras' "India cycle" - McNeece, Lucy Stone, 1940- (University Press of Florida, 1996)
Lucy Stone McNeece proposes a political reading of six of Marguerite Duras' works, centering on a single narrative core as an allegory of the neocolonial politics of representation. She argues that Duras speaks about her past in colonial Indochina both to establish an analogy between bankrupt colonial structures of the 1930s and the post-modern media culture of modern France and to alert her readers to the invisible oppression within the liberal democracies of Western Europe. Using two settings - India in the 1930s and northern France in the 1970s - Duras examines the vestiges of colonial attitudes and exclusionary, racist practices in contemporary culture and reveals the hidden structures that perpetuate these practices.